English Foreign Language (EFL) Students' Listening Strategies and the Challenges in the Digital Era - Waloyo, Edy (Foreign Language Instruction Probe, 2024)
One of the most important abilities for learning English well is the capacity to listen, both in formal and informal settings. When studying a language, listening comprehension helps students comprehend a range of spoken texts, from formal speeches to casual conversations. Students who have good listening skills are able to understand key details, determine the main points of the message, and correctly interpret meaning. The teacher's ability to plan the listening exercise aids the students in developing their listening skills. Understanding students' habits when learning to listen is the first step toward a successful teaching career. This research explains the application that was used, the listening tactics employed by the EFL students, and the challenges they had when completing the application. Eighty-two new students in the English Language Teaching Department (ELTD) comprise the research population, and 15 students were interviewed randomly. This study uses qualitative research methods. The information was gathered from observation and interviews. Coding, example-taking, and description were used to analyze the data findings. The findings indicate that when learning to listen, EFL students are more likely to employ metacognitive strategies than cognitive or socio-affective strategies. Students use YouTube, Twitter, Joox, TOEFL, Spotify, Podcasts, Dou Linggo, BBC Learning, Instagram, Praat, Google Translate, Tune In, and Pronunciation in Use as applications for learning to listen. Students face challenges when using applications due to internal factors (students and listeners) as well as external factors (Internet bandwidth and speakers). This finding should aid teachers in creating a listening lesson plan that takes into account the needs and personalities of their students.